TLR7/TLR8 activation and susceptibility genes synergize to breach gut barrier in a mouse model of lupus - Ma, Longhuan; Terrell, Morgan; Brown, Josephine; Castellanos Garcia, Abigail; Elshikha, Ahmed; Morel, Laurence (Frontiers in Immunology, 2023)
Mounting evidence suggests that increased gut permeability, or leaky gut, and the resulting translocation of pathobionts or their metabolites contributes to the pathogenesis of Systemic Lupus Erythematosus. However, the mechanisms underlying the induction of gut leakage remain unclear. In this study, we examined the effect of a treatment with a TLR7/8 agonist in the B6.Sle1.Sle2.Sle3 triple congenic (TC) mouse, a spontaneous mouse model of lupus without gut leakage. R848 decreased gut barrier integrity in TC but not in congenic control B6 mice. Immunofluorescence staining of the ileum showed a reduced expression of the tight junction protein Claudin-1, endothelial cell tight junction PECAM1, as well as an increased infiltration of immune cells, including B cells and CD11b+ cells, in R848-treated TC as compared to untreated control mice. However, NKp46+ cells which play critical role in maintaining gut barrier integrity, had a lower frequency in treated TC mice. Flow cytometry showed an increased frequency of plasma cells, dendritic cells and macrophages along with a decreased frequency of NK cells in R848 treated TC mice lamina propria. In addition, we showed that the R848 treatment did not induce gut leakage in TC.Rag1-/- mice that lack mature T and B cells. These results demonstrate that TLR7/8 activation induces a leaky gut in lupus-prone mice, which is mediated by adaptive immune responses. TLR7/8 activation is however not sufficient to breach gut barrier integrity in non-autoimmune mice.